URGENSI PENGETAHUAN PERKEMBANGAN ANAK USIA DINI TERINTEGRASI ISLAM BAGI PENDIDIK DALAM MENGHADAPI ERA PENDIDIKAN 4.0 - Fatimah Depi Susanty Harahap; Diniya (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Education 4.0 is an education program to support the creation of intelligent education. Smart education in which aims to forge skills in the form of problem-solving, working in teams, communication, critical thinking, creativity, and digital literacy. To prepare for the challenges of education in the revolutionary 4.0 era, Indonesia increased the ability and skills of human resources, especially in the field of education. To achieve the learning objectives of education 4.0, educators are required to be able to know the stages of early integrated development of Islam. This is very important because children's skills and intelligence must be formed from an early age to be able to face the challenges of the educational era 4.0. The purpose of this paper is to describe the urgency of knowledge of the development of integrated Islamic age children for educators in the face of the era of education 4.0. This research is descriptive. Research data obtained from studies and analysis sourced from books, journals, and other documents needed as needed. The result of this study is that educators can understand and realize the importance of knowledge of the development of integrated early childhood Islam in facing the challenges of education in the future. Thus educators can choose the right teaching methods for children